2021
DOI: 10.3390/w13202838
|View full text |Cite
|
Sign up to set email alerts
|

Model-Driven Strategies for Sulfide Control in a Regional Wastewater System Receiving Tannery Effluents in Portugal

Abstract: Ageing infrastructure are a concern for many wastewater utilities. This is accentuated with the presence of hydrogen sulfide within the sewer headspace, known to induce concrete corrosion, toxicity and odours. Some industrial effluents contain significant sulfide concentrations, however most field studies in the literature refer to domestic networks, or lab/pilot scale sulfide abatement strategies for varied effluents. Hence, the objectives of this work are: (1) To obtain data regarding the evolution of sulfid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…The study of the global performance of systems with the ICB and EPS by Malanho et al has shown that ETICS with ICB that reduces the environmental footprint is characterized by satisfactory global performance, similar to ETICS with EPS global performance [93]. Matos et al presented an overview of the LCA study of ETICS with ICB developed to obtain EPD according to EN 15804 and ISO 14025 [94]. Recently, Silvestre et al considered ETICS with EPS and ICB in the energetic renovation of the building envelope during a fifty-year study period.…”
Section: Etics From Academia Perspectivementioning
confidence: 99%
“…The study of the global performance of systems with the ICB and EPS by Malanho et al has shown that ETICS with ICB that reduces the environmental footprint is characterized by satisfactory global performance, similar to ETICS with EPS global performance [93]. Matos et al presented an overview of the LCA study of ETICS with ICB developed to obtain EPD according to EN 15804 and ISO 14025 [94]. Recently, Silvestre et al considered ETICS with EPS and ICB in the energetic renovation of the building envelope during a fifty-year study period.…”
Section: Etics From Academia Perspectivementioning
confidence: 99%